Ethical Assumptions: A Criticism against Modern Pragmatism - E. Korstanje, Maximiliano; Skoll, Geoffrey (International Journal of Criminology and Sociology, 2016)
The advent of neoliberalism in the early 1970s marked a new age for ethical practices. Although pragmatism as an approach to ethics pre-dated neoliberalism, the neoliberal approach to political economy ushered in a new kind of pragmatism, owing little to Jeremy Bentham, even less to the American philosophical pragmatists Charles S. Peirce, William James, and John Dewey. Today’s pragmatism has permeated the penal systems of the central countries of the world capitalist system. A new ethics emerged, a neopragmatism. Acts came to be judged by their effects and not by the motives that led to the actions. This altered the doctrine of Abrahamic religions, and led to the disappearance of forgiveness as a moral good.